THEMATIC PROGRESSION IN STUDENTS’ RECOUNT TEXTS - Sri Yunita (Institut Pendidikan Indonesia Garut, 2018)
This study aims to investigate Thematic progression patterns in students’ Recount text in a state Vocational School in Bandung. To meet the purpose, this study employs a descriptive-qualitative research design. The data are obtained from collection of students’ text. This study uses the theory of Thematic progression proposed by Halliday (1994) and Eggins (1994; 2004) as the framework to analyze the data. Furthermore, the findings show that the Thematic progression support the character of Recount text written by the students to some extents: the Theme Reiteration pattern signpost that the students tend to make the text focus by repeating the same element as Themes, the Zig Zag pattern shows that the students introduce newly information by promoting the Rheme in a clause to the Theme in the subsequent clause, and the Multiple Theme pattern specifies that the students develop the texts well according to the prior plan before writing those ideas in the text.Keywords: Thematic Progression, Students’ Text, Recount Texts